Preliminary Study of Anticoccidial Activity of Medium Chain Fatty Acids (MCFA) and their Corresponding Monoglycerides on Broiler Chicken Coccidiosis - Tan, G.H.; Long, K. (International Journal of Biotechnology for Wellness Industries, 2012)
The effect of anticoccidial from oil containing medium chain fatty acids and their corresponding monoglycerides, which known as enhanced virgin coconut oil (EVCO) was investigated. A total of 100 broiler chicks were assigned to four treatment groups. Group A, B and C were infected with 8 species of live coccidia. Group A was then treated with 30% EVCO; Group B with antibiotic (Coccisul-Q) and no treatment for Group C. Group D as control. The birds infected with live coccidia (Group A, B and C) had significantly higher in the oocyst count and showed blood in droppings appeared after 7-day post-infection (DPI), except Group D. In Group A2 at 11-day post infection/4-day post treatment (DPI 11/ DPT 4), the number of oocyst count was dropped from 132,400 o/g to 600 o/g; and in Group B2 is about 75,600 o/g to 0 o/g. However, there was no significant reducing in Group C2. A significant deduction of oocysts level in faecal and cecal dramatically after 4 days post-treatment in group treated with EVCO. However, from the observation, the performance of EVCO was not as good as in the antibiotic treated group. Nevertheless, the EVCO is a plant-based compounds, it is good and safe to be used as alternative way to control coccidiosis in poultry industries. Therefore, for EVCO consumption, the treatment must be provided weekly for long lasting protection from coccidiosis.